Emissão e absorção de gases do efeito estufa decorrentes da produção de camarão marinho (Litopeneaus vannamei) - Soares, Danyela Carla Elias (Universidade Federal Rural do Semi-Árido, 2017)
The objective of this work was to identify and quantify the flow of greenhouse gases (CH4, CO2, N2O) in Litopenaeus vannamei shrimp nurseries submitted to different culture conditions. The experiment was developed with a completely randomized design, with two treatments and four replicates simultaneously, making a total of eight experimental units. Two management systems were tested: the first one (M1) used stocking density of 92 shrimp/m², maintenance fertilization with the application of calcium nitrate and molasses, and feeding through the exclusive feed method in trays for the supply of feed . The second one (M2) used a density of 14 shrimps/m², but using maintenance fertilizations constituted only by the application of calcium nitrate, the feeding consisted of the feed offered through the volley method. The results showed that there were variations in the emission standard for the two treatments used, as well as in the concentrations of the evaluated gases. The mean values of total gas flow recorded were -314,87 mg.m².dia-1 de CH4, -3773,51 mg.m².dia-1 de CO2, 2,47 mg.m².dia-1 de N2O for M1. However, for M2, the following values were: 653,89 mg.m².dia-1 de CH4, 497,52 mg.m².dia-1 de CO2, 25,59 mg.m².dia-1 de N2O. Thus, the results obtained in this study suggest that the multiple environmental and management conditions offered in the crop interfere with the production and emission of the gases, and can act as a source or sink for these gases. In this context, it can be concluded that shrimp farming, when combined with the use of adequate operational management, with better feed utilization and adequate fertilization, has the potential to absorb some gases such as CH4 and CO2, And lower emission of N2O even using high crop densities, opposing the paradigm that the greatest environmental damage caused by shrimp farming occurs through intensive cultivation
Emission and absorption of greenhouse gases from the production of marine shrimp farm (Litopeneaus vannamei)
Keywords: Aquecimento global; Emissões animais; Gases do efeito estufa; Carcinicultura; Impactos ambientais; Global warming; Animals emissions; Greenhouse gases; Shrimp farming; Environmental impacts; CIENCIAS AGRARIAS::MEDICINA VETERINARIA